Kette na svetli strani moderne - Kmecl, Matjaž (Slavistična revija, 2006)
The purpose of this article about the "merry" Kette is not to give a detailed analysis, but to point out his distiction in the poetic world of the Moderna; the fact that he and Župančič stepped to the other, bright, and unbound hemisphere; and that Cankar, despite his unquestionable greatness, was not its only "trademark".
Keywords: humor; humour; Kette, Dragotin, 1876-1899; moderna; Moderna Therapeutics; Slovene literature; Slovene poetry; slovenska knjževnost; slovenska poezija